Kontribusi Kesalehan Ritual dan Kondisi Sosial Ekonomi Keluarga terhadap Perilaku Merusak Ekosistem Terumbu Karang - Afifi, Mansur (UI Scholars Hub, 2011)
Destructive behavior to coral reef ecosystem should not exist if community realize the importance value of theexistence of coral reefs, have adequate source for livelihood and an obedience to God Almighty. The purpose of this study is to analyze the influence of religious ritual performing (religiousness),socialand economic conditions of society ondestructive manner of community tocoral reefs. The data collected are analyzed quantitatively using structural equation model (SEM) using the method of Partial Least Square (PLS). The result findings show that the destructive behavior of the community to coral reef is not influenced by the piety of the people in performing ritual worship. The more devout people in performing ritual worship behavior does not necessarily make them more friendly to the environment, particularly coral reef ecosystems. The destructive behavior of the community to coral reef is also not influenced by their social conditions. The higher level of community's education does not necessarily make them more concerned about the environment. The destructive behavior of community tocoral reef issignificantly influenced by theeconomic conditions of society. Communities with lower income levels tend to perform acts that damage the coral reefs such as coral mining and destructive fishing techniques in an effort to satisfy their economic needs.